Simplify: (b^3/-2a^4)^3
First: distribute the exponent "3" with the term in the numerator....
*When you have a variable with an exponent raised to another - multiply the exponents....
b^(3*3)
b^9
Sec: distribute the exponent with the term in the denominator....
(- 2a^4)^3
- 2^3a^(4*3)
(-2)(-2)(-2)(a^12)
(-2)(4)(a^12)
- 8a^12
Third: combine the new results...
(b^9)/(- 8a^12)
2007-02-10 16:52:30
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
1⤋
You can take the top and bottom of the fraction to the 3rd power without changing the answer.
(b^3)^3 = b^9 because you multiply the two exponents.
-2 ^3 = -8
(a^4)^3 = a^12
So your answer is: b^9 / -8a^12
2007-02-11 00:10:31
·
answer #2
·
answered by jflinca 2
·
0⤊
0⤋
cube the top and the bottom and remember that when you raise a power to a power, the exponents multiply
b^3^3 = b^9
(-2a^4)^3 = -8a^12
b^9/-8a^12
2007-02-11 00:09:17
·
answer #3
·
answered by radne0 5
·
0⤊
0⤋
The question you have can be:
(1) (b^3/-2(a^4))^3
or
(2) (b^3/(-2a)^4)^3
(m^z)^y = m^(z*y)
For (1):
(b^3/-2(a^4))^3 = b^(3*3)/(-2)^3.a^(4*3) = b^9/-8.a^12
For (2):
(b^3/(-2a)^4)^3 = b^(3*3)/((-2)^4.a^4)^3 = b^9/(16.a^4)^3 = b^9/4096.a^12
If the original question looks EXACTLY like your question (without any additional parentheses) then the answer is as in (1).
2007-02-11 00:21:14
·
answer #4
·
answered by badaasaab 2
·
0⤊
1⤋
That's like (x/y)^3, which is x^3/y^3
So (b^3)^3 / (-2a^4)^3
= b^9 / -8a^12
2007-02-11 00:08:41
·
answer #5
·
answered by Tim P. 5
·
0⤊
0⤋
Within brackets
(!@#$%^&*)
2007-02-11 00:08:13
·
answer #6
·
answered by J.SWAMY I ఇ జ స్వామి 7
·
0⤊
2⤋